3√2*(5√2-2√6x)+4√3*(√3-2x)+√6*(8x-3√6)=
Răspunsuri la întrebare
Răspuns de
1
3√2×(5√2 - 2√6 x) + 4√3 × ( √3 - 2 x ) + √6× (8 x - 3√6) =
= 15√4 - 6√12 x + 4√9 - 8√3 x + 8√6 x - 3√36 =
= 15 × 2 - 6 × 2√3 x + 4 × 3 - 8√3 x + 8√6 x - 3 ×6 =
= 30 - 12√3 x + 12 - 8√3 x + 8√6 x - 18 =
= 42 - 18 - 20√3 x - 8√6 x =
= 24 - 20√3 x - 8√6 x=
= 4 ( 6 - 5√3 x - 2√6 x)
= 15√4 - 6√12 x + 4√9 - 8√3 x + 8√6 x - 3√36 =
= 15 × 2 - 6 × 2√3 x + 4 × 3 - 8√3 x + 8√6 x - 3 ×6 =
= 30 - 12√3 x + 12 - 8√3 x + 8√6 x - 18 =
= 42 - 18 - 20√3 x - 8√6 x =
= 24 - 20√3 x - 8√6 x=
= 4 ( 6 - 5√3 x - 2√6 x)
meliss83:
multumesc.
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă